2019
DOI: 10.1093/gji/ggz159
|View full text |Cite
|
Sign up to set email alerts
|

Detailed lithospheric structure of an arc-continent collision beneath Taiwan revealed by joint inversion of seismological and gravity data

Abstract: The largest compilation of seismological and gravimetry data are combined in a sequential inversion to shed light on unresolved crustal structures in Northern Taiwan and Southernmost Ryukyu area. Our density and seismic velocity models reveal a NW-SE trending Transfer Zone (TZ) between 23.25 • N and 24 • N. This primary TZ delimits major changes in the Eurasian Plate (EP) slab geometry and dynamics, as well as first order crustal structure variations. North of this TZ, the EP slab is breaking off from north to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…To the east of the LV is the CoR of PSP affinity, where the Moho depth and V p / V s , respectively, vary from 27 km and 1.92 beneath HGSD around 23.5°N to 15 km and 1.75 beneath FULB about 35 km to the south. Such large variations imply that the Moho geometry and crustal elastic properties under the collision suture and accreted CoR may have been disturbed drastically through subduction‐extrusion processes (Gautier et al., 2019). Both the sites yield a similarly high V p of about 6.54–6.62 km/s anticipated for the crust in an accreted oceanic arc setting.…”
Section: Resultsmentioning
confidence: 99%
“…To the east of the LV is the CoR of PSP affinity, where the Moho depth and V p / V s , respectively, vary from 27 km and 1.92 beneath HGSD around 23.5°N to 15 km and 1.75 beneath FULB about 35 km to the south. Such large variations imply that the Moho geometry and crustal elastic properties under the collision suture and accreted CoR may have been disturbed drastically through subduction‐extrusion processes (Gautier et al., 2019). Both the sites yield a similarly high V p of about 6.54–6.62 km/s anticipated for the crust in an accreted oceanic arc setting.…”
Section: Resultsmentioning
confidence: 99%
“…Backarc rifting appears to produce additional compression in the southern Ryukyu accretionary wedge as illustrated by the seismicity distribution, which suggests the rotating Yonaguni block overrides and deflects the subducting PSP, inducing a steep change in the slab geometry (Gautier et al., 2019). To estimate the relative motion between the PSP and the forearc, we estimate the differential velocities between plate convergence and backarc rifting along the Ryukyu Arc.…”
Section: Resultsmentioning
confidence: 99%
“…(2018) and Gautier et al. (2019) and (2) when the parameter relationship is included as part of the joint inversion workflow. From this second group, Tiberi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Carcione et al (2007) showed how in sedimentary environments porosity and fluids of the rock matrix can provide a physical link that causes a correlation between seismic velocities and electrical conductivities. The so-called petrophysical joint inversion has generally been approached in two ways: (1) when there is a relationship between the parameters which are used to constrain the dependent parameters, in a sequential inversion mode, for example Dufréchou et al (2018) and Gautier et al (2019) and (2) when the parameter relationship is included as part of the joint inversion workflow. From this second group, Tiberi et al (2008) retrieved linear relationships with the depth between the density and the compressional velocity in a Birch (1960) type relationship.…”
mentioning
confidence: 99%